A Comment on "The PhD Pipeline Initiative Works: Evidence from a Randomized Intervention to Help Underrepresented Students Prepare for PhDs in Political Science" - Marjorie De La Cruz; Sahar Abi-Hassan; Michael Denly (Institute for Replication (I4R), 2024)
We provide a reproduction and replication of Brutger (2024), which examines the effects of the University of California, Berkeley's Pipeline Initiative in Political Science (PIPS) program on five self-reported outcomes related to interest and preparation towards pursuing graduate school. We are able to reproduce the author's results but do note some minor coding challenges. Our additional replication analysis confirms that the study's original results are robust to different model specifications. In future analysis of PIPS, we suggest that the author address our suggestions regarding the wording of the survey questions, sample selection, and statistical power. Overall, we commend the author on a good study of an important topic.
Keywords: D63; M14; I24; I23; 330; Diversity; Equity; Inclusion; DEI; Political Science; Graduate School; Program Evaluation; Randomized Controlled Trial